Assessing the Clinical Effectiveness of Digital Mental Health Platforms: An Evidence-Based Review for Professionals - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2025)
The confluence of escalating global mental health challenges and rapid technological advancement has positioned Digital Mental Health DMH Platforms as a crit...
Keywords: Digital Health; Medical Ethics; Patient Care; Healthcare Innovation